Human fecal flora: variation in bacterial composition within individuals and a possible effect of emotional stress. - Holdeman, L V (1976)
Data are presented on the distribution of 101 bacterial species and subspecies among 1,442 isolates from 25 fecal specimens from three men on: (i) their normal diet and normal living conditions, (ii) normal living conditions but eating the controlled metabolic diet designed for use in the Skylab simulation and missions, and (iii) the Skylab diet in simulated Skylab (isolation) conditions. These bacteria represent the most numerous kinds in the fecal flora. Analyses of the kinds of bacteria from each astronaut during the 5-month period showed more variation in the composition of the flora among the individual astronauts than among the eight or nine samples from each person. This observation indicates that the variations in fecal flora reported previously, but based on the study of only one specimen from each person, more certainly reflect real differences (and not daily variation) in the types of bacteria maintained by individual people. The proportions of the predominant fecal species in the astronauts were similar to those reported earlier from a Japanese-Hawaiian population and were generally insensitive to changes from the normal North American diet to the Skylab diet; only two of the most common species were affected by changes in diet. However, one of the predominant species (Bacteroides fragilis subsp. thetaiotaomicron) appeared to be affected during confinement of the men in the Skylab test chamber. Evidence is presented suggesting that an anger stress situation may have been responsible for the increase of this species simultaneously in all of the subjects studied. Phenotypic characteristics of some of the less common isolates are given. The statistical analyses used in interpretation of the results are discussed.